Conflicts that arise in the use of digital technology in the classroom accentuated by the COVID-19 pandemic - Silva, Aline (2024)
This article aims to identify conflicts that arise in the use of digital technologies (DT) in the classroom, accentuated by the COVID-19 pandemic. The methodology of this research is part of a qualitative approach circumscribed in a documentary approach based on the analysis of the discourse of two teachers in a live produced by the Aula Aberta project and the other carried out by the Brazilian Linguistics Association (ABRALIN) during the COVID-19 pandemic, in 2020. This research is affiliated with literacy studies that consider practices with social and plural digital technologies. The results indicate that literacy practices with DT can enhance teaching. However, this perspective, in parallel, shows that several DT used in social practices previously known in the student's daily life, to be inserted in the school sphere, cause conflicts to the detriment of precarious infrastructure and the lack of specific training of many teachers regarding their pedagogical use. in the COVID-19 pandemic.